Detection Human Papilloma Virus genotype (16/18) in Iraqi Women Patients with endometrial carcinoma by using Chromogen - Insitu Hybridization (CISH) Technique - hassan, Athraa Zaidan (Iraqi Journal of Cancer and Medical Genetics, 2016)
Aim: To investigate the possible association between human papillomavirus (HPV) and endometrial carcinoma. Does HPV play any role in the initiation or prognosis of endometrial adenocarcinomas among Iraqi women patients. Method: To determine the relationship between HPV and endometrial carcinoma , a retrospective study was done. The study was carried out on 30 patients with hisopathologically confirmed primary endometrial adenocarcinoma ,samples were collected from each patients , as well as twenty (20) endometrial tissues from control individuals with no cancer. Chromogen In situ hybridization (CISH) was used to detect HPV DNA genotype 16 /18 in endometrial tissues. Results: HPV 16/18 was detected in 19/30 (63.3%) tumor sample while negative cases were 11/30 (36.7%) of tumor sample and HPV 16/18 was detected in 5/20(25.0%) of endometrial control group while negative in 15/20 (75.0%) cases of endometrial control group. Conclusion: Our results revealed that high risk of HPV(16 / 18 ) being the most frequent type in Iraqi women patients with endometrial adenocarcinoma. Association between HPV infection and endometrial adenocarcinoma was observed and this research considered the first study which evaluated score ,intensity and pattern of replication system of HPV by using CISH technique which reflected role of HPV in endometrial carcinogensis.